The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1961
DOI: 10.1084/jem.113.1.177
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Immune Human Hemolysis

Abstract: Serum complement is of potential importance to clinical medicine and to human biology in immune reactions and hypersensitivity states. However, most studies on the characteristics and mechanism of action of complement have been performed on systems largely of non-human origin (1, 2). The present studies were undertaken to study a specific immune human hemolytic disorder and to use this as a model system for the study of human complement in a reaction system involving human erythrocytes and an antibody of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 12 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…An antiserum prepared in rabbits to whole sheep red cells was heated to 560 C for 30 minutes, diluted 1/100, and stored at -200 C. 4 Human complement. Whole human serum was obtained from the blood of normal subjects by defibrination and centrifugation at 40 C. During use, the serum was 2 Kindly provided by the Lister Institute, London, England.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…An antiserum prepared in rabbits to whole sheep red cells was heated to 560 C for 30 minutes, diluted 1/100, and stored at -200 C. 4 Human complement. Whole human serum was obtained from the blood of normal subjects by defibrination and centrifugation at 40 C. During use, the serum was 2 Kindly provided by the Lister Institute, London, England.…”
Section: Methodsmentioning
confidence: 99%
“…4 Obtained from Staynes Laboratories. For each basic dilution of C' to be tested, 4.5 ml of the standard suspension of cells in VSB was mixed at 00 C 5 with 4.5 ml of antibody in the dilution optimum for normal cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these data, however, are from studies using guinea pig serum, and it is difficult to find pH optimum data dealing with classical EA immune hemolysis where human serum is the source of C'. Both Dacie (le) and Hinz, Picken, and Lepow (12) agree that the optimal pH for hemolysis of erythrocytes in the C'-dependent Donath-Landsteiner antibody hemolytic system is between 7 and 8. Recent studies on the pH optimum for C'-dependent bacteriolysis by human serum have shown that the system functions best at pH 8.4 (13).…”
mentioning
confidence: 82%
“…The Donath-Landsteiner (D-L) reaction is suitable for this purpose, as previously indicated (4), because the antibody is an active hemolysin but a poor agglutinin and because the biphasic nature of the hemolytic reaction is readily susceptible to study of early and late phases of complement action separately.…”
Section: Introductionmentioning
confidence: 99%